Challenges in Diagnosing Functional Visual Loss and Malingering: a Case Report: Poster Presentation - Case Report - General practitioner - Rona Ali Badjrai; Sarah Shabrina; Subandono Bambang Indrasto; Arlin Chyntia Dewi (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Functional Visual Loss (FVL) is decreased visual acuity and/or altered visual fields without any associated organic pathology and is considered within the spectrum of malingering. It manifests as either simulating an ophthalmic disease or denying ophthalmic disease. Thorough history-taking and careful examination of the patient are essential in reaching the diagnosis. Case Illustration : A 17-year-old female came with complaints of a spinning headache, sudden and painless blurry vision in both eyes, double vision, and a history of syncope for the last two days. Ophthalmology examination revealed UCVA was 0.5/60 for both eyes with inconsistent answers from the patient. The confrontation test, light reflex, funduscopy, Humphrey visual test, OCT, and MRI were normal. Malingering was suspected and a psychiatric consultation was made. The patient was found to be a victim of bullying and had a history of visual hallucinations. The patient was then diagnosed with severe depression with psychotic signs. Discussion : Conclusion : FVL can be suspected when there is inconsistency in the results of some clinical basic tests. Despite the association between FVL and psychological problems like depression is complicated, this condition may occur in a bidirectional relationship in which depression leads to disability or contrarily. In conclusion, diagnosing visual problems in malingering patients can be challenging. Subjective and objective tests are needed to help practitioners confirm the malingering state of the patient. Practitioners also should be aware of the underlying risk of psychological problems among persons reporting visual function loss.